Comparison of summer and spring carbon dioxide vertical and spatial distribution over the Southwest Indian Ocean Islands using TES data - (:unkn) unknown (My University, 2016)
Southwest Indian Ocean (SWIO) Islands States are vulnerable to environmental hazards, caused by pressure on the environment to satisfy the socio-economic needs of growing human population. The forests of these tropical islands are rich in biodiversity and they are large carbon sinks. Rapid population growth in these islands is identified as one of the main factors responsible for deforestation, which in turn is the main source of carbon dioxide (CO2) emissions. This study is born from the Agence Universitaire de la Francophonie (AUF) programme called observation des Risques naturels en Milieux Insulaires (RAMI). In this study we contrast the CO2 3-dimensional atmospheric loading between the wet austral summer and dry spring seasons, and compare the relative CO2 loading over the Comoros, Madagascar, Reunion and Mauritius islands. We found there is a general shift to higher concentrations from summer to spring season and the CO2 concentration is highest at the southern part of Madagascar in both seasons. This study also illustrates the influence of source strength and meteorology.
Keywords: African Research